Long-term administration of bumetanide improve functional recovery after spinal cord injury in rats - Hashemizadeh, Shiva; Gharaylou, Zeinab; Hosseindoost, Saereh; Sardari, Maryam; Omidi, Ameneh; Hosseini ravandi, Hassan; Hadjighassem, Mahmoudreza (Frontiers in Pharmacology, 2022)
Ion disturbances are among the most remarkable deficits in spinal cord injury (SCI). GABA is an integral part of neural interaction. Action of the GABAA receptor depends on the amount of intracellular chloride. Homeostasis of chloride is controlled by two co-transporters, NKCC1 and KCC2. Previous studies revealed that NKCC1 are disturbed in SCI. In this study, NKCC1 is highly expressed in the epicenter of the lesioned spinal cord at 3 hours after induction of the lesion and reached the peak around 6 hours after SCI. Bumetanide (2 and 4 mg/day), as a specific NKCC1 inhibitor, was used at 3 hours post SCI for 28 days. The functional recovery outcomes were measured by the Basso–Beattie–Bresnahan (BBB) locomotor rating scale, ladder walking test, and hot plate test. The rats that received bumetanide 4 mg/day exhibited improved recovery of locomotor function, reduction of NKCC1 gene expression, and upregulation of GAP protein levels 28 days post SCI. Histological tissue evaluations confirmed bumetanide’s neuroprotective and regenerative effects. This study provides novel evidence for the benefits of bumetanide in early administration after SCI.